Comorbid diabetes and the risk of progressive chronic kidney disease in HIV-infected adults: data from the Veterans Aging Cohort Study. - Medapalli, Raj K; Parikh, Chirag R; Gordon, Kirsha; Brown, Sheldon T; Butt, Adeel A; Gibert, Cynthia L; Rimland, David; Rodriguez-Barradas, Maria C; Chang, Chung-Chou H; Justice, Amy C; He, John Cijiang; Wyatt, Christina M (Journal of acquired immune deficiency syndromes (1999), 2012)
Approximately, 15% of HIV-infected individuals have comorbid diabetes. Studies suggest that HIV and diabetes have an additive effect on chronic kidney disease (CKD) progression; however, this observation may be confounded by differences in traditional CKD risk factors.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Aging; Cohort Studies; Comorbidity; Diabetes Complications; Disease Progression; Female; HIV Infections; Humans; Male; Middle Aged; Renal Insufficiency, Chronic; Risk Assessment; Veterans; Young Adult